Can Value Capture work in a car dependent city? Willingness to pay for transit access in Perth, Western Australia - McIntosh, James; Trubka, Roman; Newman, Peter (Pergamon, 2014)
This paper investigates the impact of transit on urban land markets in the highly car dependent corridors of Perth with a focus on where new fast rail transit services have recently been built. It determines people’s willingness to pay for transit access within different pedestrian catchments for each of the corridors based on hedonic price modelling using land value data on over 460,000 households. The case study uses cross sectional and panel data hedonic price modelling methodology for the calculation of willingness to pay for transit. It finds that land market increases of up to 40% can be achieved, and is particularly relevant to car dependent cities looking to capture the financial and economic value created to build transit extensions or entirely new systems, thus making a strong case for value capture funding of transit projects into car dependent suburbs and the potential for density increases near stations.